Wo steht der Osten? Eine ökonomische Analyse anhand von Wohlfahrts- und Happinessindikatoren - Björn A. Kuchinke; Heike Walterscheid (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2005)
German media repeatedly discuss the thesis, that residents in East Germany are dissatisfied with their life situation in comparison to those in West Germany. Therefore East Germans tend to moan. One intention of this essay is to answer the question, whether the East Germans are in fact dissatisfied with their life situation. Due to empirical evidence the question posed is to be answered with yes. The second intention is to examine the reasons for the discontent of residents in East Germany. For this purpose the analysis bases at first on classical economic indicators like the gros domestic product and the income. Secondly socio-economic operating figures like the development of life expectancy and the body size are considered. Third the social capital of a society as a welfare-affecting factor rounds off the analysis.
Keywords: 330